Penerapan Maksim Grice dalam Iklan Jual Beli Gadget pada Komunitas r/AppleSwap: Analisis Pragmatik dan Wacana - Syaifudin, Nanang; Cholsy, Hayatul (Humanis; Vol 29 No 2 (2025), 2025)
This study examines the application of Grice's maxims in gadget buying and selling ads in the r/AppleSwap community on Reddit. Using a combined qualitative-quantitative approach with pragmatic discourse analysis, the research explores the use of four maxims—quantity, quality, relevance, and manner—across 104 ads posted in September to December 2024. Data were collected using scraping through the PullPush API Reddit Search and documentation. The data were then analyzed qualitatively to examine the application of maxims and quantitatively to calculate the frequency of violations. The findings show that most ads adhere to the maxims, particularly in relevance, though violations were noted in the quantity maxim. These results suggest that adhering to Grice's maxims improves communication effectiveness, fosters trust between sellers and buyers, and promotes transparency in online transactions, contributing to more successful exchanges in the r/AppleSwap community.